2010
DOI: 10.1038/onc.2010.570
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 1 expression is inhibited by p16INK4a at the post-transcriptional level through the microRNA pathway

Abstract: The p16INK4a protein regulates cell cycle progression mainly by inhibiting the activity of G1-phase cyclin-dependent kinases (CDKs) 4 and 6, the subsequent retinoblastoma protein (pRb) phosphorylation and E2F transcription factor release. The p16INK4a protein can also repress the activity of other transcription factors, such as c-myc, nuclear factorkappaB and c-Jun/AP1. Here, we report that, in two p16WT and p53 WT cell lines (MCF7 and U87), p16INK4a overexpression induces a dramatic decrease in CDK1 protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 50 publications
(59 reference statements)
3
43
0
Order By: Relevance
“…This observation is surprising because previously published data suggested that miR-650 is expressed independently of immunoglobulin genes. [12][13][14][15] We subsequently performed a bioinformatical analysis of the upstream region (500 nt) of the miR-650 and IgL leader exon by search for Polymerase II promoter sequence (PROSCAN 18 ) and transcription elements (TESS System 19 ). This confirmed that the IgL and miR-650 gene likely use the same major promoter region Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation is surprising because previously published data suggested that miR-650 is expressed independently of immunoglobulin genes. [12][13][14][15] We subsequently performed a bioinformatical analysis of the upstream region (500 nt) of the miR-650 and IgL leader exon by search for Polymerase II promoter sequence (PROSCAN 18 ) and transcription elements (TESS System 19 ). This confirmed that the IgL and miR-650 gene likely use the same major promoter region Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, expression of miR-650 is clearly not strictly dependent on IgL promoter, since it is expressed in all CLL cells and also in other cell types. [12][13][14][15] This suggests that IgL promoter rather serves as a potent enhancer element for miR-650. It is known that, similarly to miR-650, a fraction of microRNAs is located in exons of protein-coding genes, 20 but the data about the regulation of their expression is limited.…”
Section: The Role Of Mirna-650 In B Cells and Cll 2111mentioning
confidence: 99%
See 3 more Smart Citations